PROTOTYPE DESIGN OF SMART COOP WARMING SYSTEM (SCOWAS) WITH GASIFICATION METHOD USING WOOD PELLETS IN BROILER LIVESTOCK - Maharani, Ni Wayan Cantika; Permatasari, Komang Rianti Arista (Jurnal TAM (Technology Acceptance Model), 2024)
Broiler chickens are a livestock business in great demand by the public because the harvest period is relatively fast and has high economic value. The initial growth phase of broiler chicks is an important stage that breeders must pay attention to. Broiler chickens will grow optimally if they are supported by environmental factors and appropriate care. One of the challenges for broiler chicken breeders is managing temperature and humidity in the cage, especially during the starter phase. In the starter phase, namely, chickens aged 0-14 days, chickens are not yet able to regulate their body temperature so breeders use machines to help get the optimal temperature. This cage heating machine uses fuel, namely Liquefied Petroleum Gas (LPG). The challenge currently faced by chicken farmers is the difficulty of obtaining LPG fuel, especially 3 kg in large quantities. The availability of LPG fuel can cause shortages at certain periods, thus affecting the optimization of the cage heating system. In this research, a prototype SCOWAS (Smart Coop Warming System) machine has been designed which can meet the optimal temperature and humidity requirements of the cage and uses wood pellets as an alternative fuel. The expected result of this research is to develop a conventional chicken coop heater as an alternative and efficient solution for the sustainability of broiler chicken farming in the agricultural and livestock sectors.